CO2 Capture by Carbon Aerogel–Potassium Carbonate Nanocomposites - Guang Yang; Hongchao Luo; Tomonori Ohba; Hirofumi Kanoh (International Journal of Chemical Engineering)
Recently, various composites for reducing CO2 emissions have been extensively studied. Because of their high sorption capacity and low cost, alkali metal carbonates are recognized as a potential candidate to capture CO2 from flue gas under moist conditions. However, undesirable effects and characteristics such as high regeneration temperatures or the formation of byproducts lead to high energy costs associated with the desorption process and impede the application of these materials. In this study, we focused on the regeneration temperature of carbon aerogel–potassium carbonate (CA–KC) nanocomposites, where KC nanocrystals were formed in the mesopores of the CAs. We observed that the nanopore size of the original CA plays an important role in decreasing the regeneration temperature and in enhancing the CO2 capture capacity. In particular, 7CA–KC, which was prepared from a CA with 7 nm pores, exhibited excellent performance, reducing the desorption temperature to 380 K and exhibiting a high CO2 capture capacity of 13.0 mmol/g-K2CO3, which is higher than the theoretical value for K2CO3 under moist conditions.